Unequal Czech Old Age Pensions for Men and Women in the ECtHR’s Case Law with Special Regard to Andrle v. the Czech Republic - Stefko , Martin (The ECHR at 70: The Central European Narrative, 2025)
The purpose of this article is to provide an overview of the Czech pension policy in the light of Mr Andrle’s case and to present the underlying argumentation. How is it possible that Mr Andrle did not win the case, although he had suffered discrimination to the extent that he was obliged to collect additional 4 years and 20 months of insured periods? As a woman, no such additional period would have been required. Despite the obvious gender-based discrimination, neither the Constitutional Court of the Czech Republic nor the ECtHR dared to declare this to be a discrimination. The former supported the explanation with the reasoning that there was nothing to do as the advantageous pension insurance status of women could only be abolished but not replicated to the status of men and that everything was covered by the people’s power. The ECtHR argued that this practice was to be stopped, was going to be stopped by the policymakers, but Czechs simply needed more time. Czechs have had more time, but the will of the people remained more or less the same.Keywords: pension insurance, old age, caretakers